(untitled) (Research, Society and Development, 2021)
To understand the perception of undergraduate nursing students about the consequences of inadequate handling of sanitary waste. This is a descriptive and analytical field investigation with a qualitative approach, carried out with nine students from the 4th, 6th and 7th period. Data collection was performed using the focus group technique. The data obtained were organized and analyzed giving rise to three categories, namely: social and environmental risks, occupational risks and unnecessary expenses. It was found that the inadequate management of sanitary waste is directly related to the production of risks in the social, environmental and occupational dimensions. In addition to compromising the economic dimension of the already precarious health sector. The subject requires broad and critical reflection, so it is necessary for students to understand that such negative action is not limited only to the local level, but above all to the global level.